Measuring Substance-Related Disorders Using Canadian Administrative Health Databanks: Interprovincial Comparisons of Recorded Diagnostic Rates, Incidence Proportions and Mortality Rate Ratios. (February 2022) - Huỳnh, Christophe; Kisely, Steve; Rochette, Louis; Pelletier, Éric; Morrison, Kenneth B.; Li, Shelley; Hopkin, Gareth; Smith, Mark; Burchill, Charles; Lin, Elizabeth; Asbridge, Mark; Jutras-Aswad, Didier; et al.
Context: Assessing temporal changes in the recorded diagnostic rates, incidence proportions, and health outcomes of substance-related disorders (SRD) can inform public health policymakers in reducing harms associated with alcohol and other drugs. Objective: To report the annual and cumulative recorded diagnostic rates and incidence proportions of SRD, as well as mortality rate ratios (MRRs) by cause of death among this group in Canada, according to their province of residence. Methods: Analyses were performed on linked administrative health databases (AHD; physician claims, hospitalizations, and vital statistics) in five Canadian provinces (Alberta, Manitoba, Ontario, Québec, and Nova Scotia). Canadians 12 years and older and registered for their provincial healthcare coverage were included. The International Classification of Diseases (ICD-9 or ICD-10 codes) was used for case identification of SRD from April 2001 to March 2018. Results: During the study period, the annual recorded SRD diagnostic rates increased in Alberta (2001–2002: 8.0‰; 2017–2018: 12.8‰), Ontario (2001–2002: 11.5‰; 2017–2018: 14.4‰), and Nova Scotia (2001–2002: 6.4‰; 2017–2018: 12.7‰), but remained stable in Manitoba (2001–2002: 5.5‰; 2017–2018: 5.4‰) and Québec (2001–2002 and 2017–2018: 7.5‰). Cumulative recorded SRD diagnostic rates increased steadily for all provinces. Recorded incidence proportions increased significantly in Alberta (2001–2002: 4.5‰; 2017–2018: 5.0‰) and Nova Scotia (2001–2002: 3.3‰; 2017–2018: 3.8‰), but significantly decreased in Ontario (2001–2002: 6.2‰; 2017–2018: 4.7‰), Québec (2001–2002: 4.1‰; 2017–2018: 3.2‰) and Manitoba (2001–2002: 2.7‰; 2017–2018: 2.0‰). For almost all causes of death, a higher MRR was found among individuals with recorded SRD than in the general population. The causes of death in 2015–2016 with the highest MRR for SRD individuals were SRD, suicide, and non-suicide trauma in Alberta, Ontario, Manitoba, and Québec. Discussion: Linked AHD covering almost the entire population can be useful to monitor the medical service trends of SRD and, therefore, guide health services planning in Canadian provinces.